2016
DOI: 10.1007/s10900-016-0253-z
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, Perception of Risk and Behaviors Related to Retail Marijuana Among a Sample of Colorado Youth

Abstract: Youth marijuana use is a growing concern with increasingly permissive views towards marijuana use. Little is known about attitudes and beliefs toward marijuana use among youth in the context of legalization. This study describes youth attitudes and beliefs about health risks associated with marijuana use, social norms of peer use, conversations with parents about marijuana use, and knowledge of recreational marijuana laws, using a venue-day-time sampling approach with diverse Colorado youth (n = 241) post-lega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Individuals who perceive a substance such as cannabis to be high risk are generally less likely to use it, and vice versa [ 34 ]. When young people are made aware that use behaviors are not normative and their misperceptions about how many of their peers actually use substances are corrected, substance use behaviors tend to decrease [ 40 , 41 ]. However, existing work from US contexts that have legalized medical and/or nonmedical cannabis are less clear, and the relationship between perceived risk, health knowledge, and use behaviors remains poorly understood with respect to cannabis [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who perceive a substance such as cannabis to be high risk are generally less likely to use it, and vice versa [ 34 ]. When young people are made aware that use behaviors are not normative and their misperceptions about how many of their peers actually use substances are corrected, substance use behaviors tend to decrease [ 40 , 41 ]. However, existing work from US contexts that have legalized medical and/or nonmedical cannabis are less clear, and the relationship between perceived risk, health knowledge, and use behaviors remains poorly understood with respect to cannabis [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding parallels the reports of counselors of increased incidences of psychosis, cognitive impairment, and other adverse consequences of cannabis use. Additionally, some researchers (e.g., Bull et al, 2017; Cerdá et al, 2017) have found a growing perception, especially among youth, that marijuana is not harmful. For this reason, the counselors in this study may have perceived greater resistance from clients regarding their marijuana use.…”
Section: Discussionmentioning
confidence: 99%
“…Irrespectively, these risk behavior rates are high and disconcerting overall. They are likely facilitated by multiple factors, including common beliefs about non-existent, or only very limited ‘impairment’ effects of cannabis, as well as a low likelihood of apprehension under current enforcement for cannabis-impaired driving ( Bull et al, 2017 , Davis et al, 2016 , Goodman et al, 2019 , Watson et al, 2019a , Watson et al, 2019b ). These circumstances urgently require intensified targeted education and enforcement efforts.…”
Section: Discussionmentioning
confidence: 99%